Acoustic gunshot detection systems: a quasi-experimental evaluation in St. Louis, MO - Mares, Dennis (Journal of experimental criminology, 2021)
Objectives The primary aim of this study is to provide an evaluation of St. Louis’ Acoustic Gunshot Detection System’s (AGDS) ability to reduce gun violence. Methods The study design is a quasi-experimental longitudinal panel study. We measure a variety of gun-related offenses across multiple treatment and control neighborhoods using a difference-in-difference approach. Because treatment neighborhoods were added to the experiment over time, changing experimental conditions, three separate study periods were examined. Results Results indicate AGDS has a mixed relationship to police response time and does not significantly reduce violent crime levels in any of the study periods. We do find consistent and substantial reductions (around 30%) in citizen-initiated calls for service for shots fired, but once new calls for AGDS are added, an overall 80% increase in gunshot responses is found. Conclusions Although the study is limited to one city, results indicate AGDS may be of little benefit to police agencies with a pre-existing high call volume. Our results indicate no reductions in serious violent crimes, yet AGDS increases demands on police resources.